Aturan Hukum Terhadap Atlet E-Sport Terkait Kontrak Kerja - Seri Mughni Sulubara; Amrizal Amrizal; Ashari Efendi; Zainal Abidin; Budiman Budiman (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
E-sport is a new electronic sport that involves competing in video games. E-sports is known as a sport that uses gaming as its field. Growing e-sports provides many benefits to players who want to become pro players or e-sports athletes. The form of legal protection that can be given to e-sport athletes is preventive and repressive, one of which is done through an employment agreement contract with athletes, so that the employment agreement contract can be a form of legal remedy in employment agreements related to wages. This study aims to determine how the legal rules apply to e-sport athletes regarding employment contracts. The method used is a qualitative descriptive research method of empirical legal nature. The data collection technique or instrument used is library research by studying various books as literature, official documents, laws and regulations, results of previous research, and other literature sources related to the problem under study. The results showed that the most important and fundamental legal protection is contained in the employment agreement. This work agreement will be the legal umbrella for the legal relationship between the athlete and the e-sport team as the provider. The legal rules for e-sport athletes related to employment contracts are regulated in the Indonesian Electronic Sports Management Board Regulation Number: 034 / PB-ESI / B / VI / 2021 concerning the Implementation of Electronic Sports Activities in Indonesia and Law No. 11 of 2022 concerning Sports.